Social Culture of Tuvans and Online Space - Lamazhaa, Chimiza K. (The New Research of Tuva, 2021)
The article analyzes the issue of how modern technologies have become, among other things, a sort of vehicles of archaization for Tuvans, i.e. of the process of returning to archaic social and cultural ties and meanings. The source of the data is the author’s survey of Tuvans who use social networks and messaging apps. The survey was conducted in early 2021 by random sampling, covering 205 people who answered the questionnaire published on Google Forms.Today Russian cyberethnography is more focused on studying the presentation of ethnicity on the Internet. The author suggests going further and considering the network as a new space for the functioning of an ethnic group’s social culture in the case of Tuvans. The analysis is based on the ideas of the anthropologists Ch. Hine and H. Rheingold. This allows us to talk about a network sociality as a fact of social reality.The development of wireless Internet in Tuva has led to the same results as all over the globe — people have learned to act together in conditions that previously did not permit this. A significant number of Tuvans use chat groups (of relatives, colleagues, friends) in messaging apps, especially on Viber. Communication via them has various social “consequences”. Most often, Viber is used to communicate with friends and relatives (90.2%). The groups of relatives number from 13 to 70 people, communication in them is flowing almost constantly, typically in the Tuvan language; participants exchange information, news, and arrange collective actions. The use of web communications as a tool for unity and coordination of actions allows Tuvans to vote in online contests of various kinds as effectively as possible.A historical insight allows us to see that the space of the social culture of Tuvans has undergone changes throughout history, and the social culture has preserved its basic values — the significance of social ties among kin groups.
Keywords: Tuvans; Tuva; social culture; space; understanding of space; worldview; social network; messaging app; kin group